2021
DOI: 10.1111/1471-0528.16949
|View full text |Cite
|
Sign up to set email alerts
|

Genital mycoplasma infection and spontaneous preterm birth outcome: a prospective cohort study

Abstract: Objective To assess the risk of spontaneous preterm birth (sPTB) associated with genital mycoplasma infection in asymptomatic women.Design Prospective cohort.Setting Public and private health services in Ribeirão Preto, SP, Brazil.Population A cohort of 1349 asymptomatic women with a singleton pregnancy at 20-25 weeks of gestation.Methods Participants completed a sociodemographic and clinical history questionnaire during the prenatal visit and provided cervicovaginal samples for the evaluation of Mycoplasma ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…1 In his letter to the editor, Prof. Dr Kotaska bring up an important point about the methodology of our study. 2 Throughout his letter, he describes the concern that women at our study with a positive culture for genital mycoplasmas and bacterial vaginosis were treated, as treatment would have the capacity to reduce the presence of these pathogens and influence their ability to cause preterm birth. 3 Because there is no routine testing and treatment guidance for genital mycoplasma infections during prenatal, we decided to orient women about possible treatment and followed with the medication due to ethical issues involved in the knowledge of the diagnosis.…”
Section: Genital Mycoplasma Infection and Spontaneous Preterm Birth O...mentioning
confidence: 99%
“…1 In his letter to the editor, Prof. Dr Kotaska bring up an important point about the methodology of our study. 2 Throughout his letter, he describes the concern that women at our study with a positive culture for genital mycoplasmas and bacterial vaginosis were treated, as treatment would have the capacity to reduce the presence of these pathogens and influence their ability to cause preterm birth. 3 Because there is no routine testing and treatment guidance for genital mycoplasma infections during prenatal, we decided to orient women about possible treatment and followed with the medication due to ethical issues involved in the knowledge of the diagnosis.…”
Section: Genital Mycoplasma Infection and Spontaneous Preterm Birth O...mentioning
confidence: 99%
“…A subgroup analysis comparing the newborn birthweight and head circumference could be instrumental in solving this dilemma. Previous studies by Vik et al 2 from Norway had demonstrated similar outcomes in neonatal survival as well. In the absence of a significant difference in newborn birthweight and head circumference, social issues need due consideration.…”
Section: Re: Obstetric Anal Sphincter Injury By Maternal Origin and L...mentioning
confidence: 57%
“…1 First, we would like to comment on the nature of the population selected for our study. 2 Due to the registry-based study design of our study, we depend on the classifications from the Population Registry. Thus, the category of foreign-born women with Norwegian-born parents is a case-mix consisting of adoptees as well as children born to Norwegian couples coincidentally living abroad at the time of the birth.…”
Section: Authors' Reply Re: Obstetric Anal Sphincter Injury By Matern...mentioning
confidence: 99%
“…We would also like to thank Prof. Dr Kotaska and his colleagues for their interest in our paper and for taking the time to express their concerns. 1 In his letter to the editor, Prof. Dr Kotaska bring up an important point about the methodology of our study. 2 Throughout his letter, he describes the concern that women at our study with a positive culture for genital mycoplasmas and bacterial vaginosis were treated, as treatment would have the capacity to reduce the presence of these pathogens and influence their ability to cause preterm birth.…”
Section: Genital Mycoplasma Infection and Spontaneous Preterm Birth O...mentioning
confidence: 99%
“…Sir, In their recent paper, Cunha et al analysed data from a diverse group of 1349 Brazilian women who participated in a 2011 study evaluating aetiological factors associated with preterm birth. 1 Women were interviewed and examined at 20-25 weeks of gestation, and cervicovaginal cultures were taken for mycoplasma, ureaplasma and bacterial vaginosis. Women were followed until delivery, and clinical associations with preterm birth were evaluated.…”
Section: Re: Genital Mycoplasma Infection and Preterm Birth Outcome: ...mentioning
confidence: 99%